Conceptual Design of an ESP32-Ultrasonic-Based Patient Visitor Counting System for Health Information Education - Alman Arapa; Selvi Mayang Sari; Rika Setyowati; Ahmad Musawwir; Sarwono (Journal of Information Systems and Technology Research, 2026)
This study presents a conceptual design of an ESP32-based patient visitor counting system for healthcare registration units and its potential use as a practical learning medium for Medical Records and Health Information (RMIK) students. The Rational Unified Process (RUP) was used to structure the design into inception, elaboration, construction, and transition activities. The resulting conceptual outputs comprise a registration-area layout, system architecture, flowchart, wiring diagram, and 16×2 LCD display design. The proposed architecture uses an ESP32 microcontroller, two HC-SR04 ultrasonic sensors for sequential detection of inbound and outbound movement, a 16×2 I2C LCD for local display, and a buzzer for event feedback, with Wi-Fi connectivity reserved for future IoT-based monitoring. The study does not report experimental prototype performance; therefore, detection accuracy, counting error, response latency, detection distance, and inbound/outbound classification accuracy remain to be validated through physical implementation and repeated trials. The contribution is primarily an application-oriented conceptual architecture connecting automated visitor-flow monitoring in healthcare registration with technology-supported RMIK education